Acrylic resin emulsion, its manufacturing method, and coating composition
The acrylic resin emulsion, formulated with specific monomers and a polymer emulsifier, addresses the challenge of achieving transparency and water resistance in saltwater environments, resulting in a coating film with enhanced properties and environmental safety.
Patent Information
- Application Number
- JP2021052151
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-25
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2041-03-25
AI Technical Summary
Existing acrylic resin emulsions struggle to achieve a balance between transparency and water resistance, particularly in saltwater environments, while also being environmentally friendly and safe for use in water-based systems.
The development of an acrylic resin emulsion that incorporates a polymerizable group-containing triorganosilyl ester monomer, (meth)acrylic acid alkyl ester monomers, and a specific polymer emulsifier, which are emulsified and polymerized to produce a coating film with enhanced transparency, water resistance, salt water resistance, and water repellency.
The resulting acrylic resin emulsion provides a transparent, water-resistant, saltwater-resistant, and water-repellent coating film, while being environmentally friendly and safe for use in water-based systems, with excellent long-term storage stability and a minimum film forming temperature of 50°C or less.
Smart Images

Figure 0007671164000001 
Figure 0007671164000002 
Figure 0007671164000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic resin emulsion, more particularly to an acrylic resin emulsion capable of forming a coating film excellent in transparency, water resistance, salt water resistance and water repellency, and a method for producing the same, and further to a coating composition containing the emulsion. [Background technology]
[0002] Conventionally, oil-based resins, rosin-based resins, vinyl-based resins, acrylic-based resins, chlorinated rubber-based resins, etc. have been widely used as binders for paints for articles to be used underwater or in seawater, but all of these have been solvent-diluted types.
[0003] However, in recent years, due to environmental concerns, the dispersion medium has been shifting from organic solvent-based to water-based. Acrylic resin emulsions are commonly used because of the ease of design, with many types of monomers available. However, acrylic resin emulsions that use surfactants often have poor water resistance, although they are highly transparent.
[0004] In order to solve this problem, development of acrylic resin emulsions with improved water resistance is underway. JP-A-7-268022 discloses an acrylic resin emulsion obtained by emulsion polymerization using a water-soluble salt of a modified styrene-(meth)acrylic acid ester-unsaturated carboxylic acid copolymer as a protective colloid. JP-A-2008-280469 discloses that an acrylic aqueous emulsion composition using PVA as a dispersant has high water resistance.
[0005] However, while these methods provide water resistance, they can impair the transparency of the film. When used as a paint, the loss of transparency leads to a dull color of the paint, so there is a need to develop an acrylic resin emulsion that is both transparent and water resistant.
[0006] On the other hand, triorganosilyl group-containing monomers have been known as monomers having water resistance. For example, JP2005-82725A and WO2017 / 164283A disclose coating compositions containing copolymers of triisopropylsilyl methacrylate and acrylic monomers. However, since both are organic solvent-based compositions, there is a risk of health damage from the viewpoint of VOC regulations and exposure of paint workers to organic solvents, and therefore the development of aqueous environment-friendly emulsions is desired.
[0007] Japanese Patent Application Laid-Open No. 2006-052284 discloses an aqueous dispersion obtained by emulsion polymerization of a mixture containing triisopropylsilyl methacrylate and other polymerizable unsaturated monomers. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 7-268022 [Patent Document 2] JP 2008-280469 A [Patent Document 3] JP 2005-82725 A [Patent Document 4] WO2017 / 164283 [Patent Document 5] JP 2006-052284 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, the aqueous dispersion described in Patent Document 5 above leaves room for improvement in terms of transparency and salt water resistance. The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an acrylic resin emulsion that gives a coating film having transparency, water resistance, salt water resistance and water repellency, a method for producing the same, and a coating composition. [Means for solving the problem]
[0010] As a result of intensive research conducted by the present inventors in order to achieve the above-mentioned object, they have found that an acrylic resin emulsion obtained by emulsifying and polymerizing (A) a polymerizable group-containing triorganosilyl ester monomer, (B) a (meth)acrylic acid alkyl ester monomer, and (C) any other polymerizable group-containing monomer in the presence of (D) a specific polymer emulsifier, gives a coating film having transparency, water resistance, salt water resistance, and water repellency, and have thus completed the present invention.
[0011] Accordingly, the present invention provides the following acrylic resin emulsion, its production method, and coating composition. (A) 20 to 80 parts by mass of a polymerizable group-containing triorganosilyl ester monomer, (B) 20 to 80 parts by mass of a (meth)acrylic acid alkyl ester monomer having no functional group, and (C) 0 to 60 parts by mass of a polymerizable group- and functional group-containing monomer other than the components (A) and (B) (provided that the total of (A) to (C) is 100 parts by mass) Acrylic resin, which is a polymer of (D) a polymer emulsifier having a number average molecular weight of 1,000 or more, 5 to 70 parts by mass per 100 parts by mass of the total of the components (A) to (C) and water. In the present invention, the term "(meth)acrylic acid alkyl ester monomer" refers to at least one of an acrylic acid alkyl ester monomer and a methacrylic acid alkyl ester monomer. The term "polymeric emulsifier" refers to an emulsifier having a high molecular weight. More specifically, it is a polymeric compound having an emulsifier function. Effect of the Invention
[0012] The acrylic resin emulsion of the present invention can provide a coating film having transparency, water resistance, salt water resistance, and water repellency. The coating film obtained from the coating composition containing the emulsion has excellent water resistance and color development. In addition, since the emulsion of the present invention is water-based, it has great advantages in terms of workability and environment. Furthermore, the emulsion of the present invention has excellent long-term storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The acrylic resin emulsion of the present invention can be produced by emulsion polymerization of (A) a polymerizable group-containing triorganosilyl ester monomer, (B) an acrylic acid alkyl ester monomer and / or a methacrylic acid alkyl ester monomer, and (C) optionally, other functional group-containing monomer copolymerizable with the (A) component and the (B) component, in the presence of (D) a specific polymer emulsifier. Each component will be described in detail below.
[0014] (A) Polymerizable group-containing triorganosilyl ester monomer The polymerizable group-containing triorganosilyl ester monomer is a monomer having a triorganosilyl group and a polymerizable group. The polymerizable group is, for example, a monovalent hydrocarbon group having a polymerizable unsaturated double bond, a carbon number of 2 to 24, and optionally having a heteroatom, such as a group derived from (meth)acrylic acid, 4-pentenoic acid, maleic acid, or fumaric acid.
[0015] The component (A) is preferably represented by the following general formula (I). [ka] R 1 is a monovalent organic group having 2 to 24 carbon atoms and optionally having a heteroatom, which has a polymerizable unsaturated double bond, and R 2 ~R 4 are each independently a monovalent linear or branched hydrocarbon group having 3 to 10 carbon atoms, or a monovalent cyclic hydrocarbon group having 3 to 10 carbon atoms.
[0016] In the above formula (I), R 1 is a monovalent organic group having a polymerizable unsaturated double bond, which may have a heteroatom, and which has 2 to 24 carbon atoms, preferably 2 to 15 carbon atoms, and more preferably 2 to 10 carbon atoms. For example, it is a monovalent hydrocarbon group having a polymerizable unsaturated double bond, which has 2 to 10 carbon atoms, preferably 2 to 6 carbon atoms, and more preferably the groups shown below. [ka]
[0017] In the monovalent organic group which may have a heteroatom, the heteroatom is an oxygen atom, a nitrogen atom, a silicon atom, etc. More specifically, it is a monovalent hydrocarbon group having a polymerizable unsaturated double bond and a heteroatom, and having 2 to 24 carbon atoms, preferably 2 to 10 carbon atoms, and is preferably a group represented by the following formula. [ka]
[0018] In the above, R 5 Examples of the alkyl group include linear, branched, or cyclic alkyl groups, unsaturated alkyl groups, and aralkyl groups having 1 to 8 carbon atoms. Examples of the linear or branched alkyl groups having 1 to 8 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, s-butyl, t-butyl, 2-methylbutyl, 2-ethylbutyl, n-pentyl, 3-methylpentyl, hexyl, heptyl, and octyl groups. Examples of the cyclic alkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups. Examples of the unsaturated alkyl groups include 2-propenyl, 2-butenyl, 3-butenyl, 2-pentenyl, 3-pentenyl, and 4-pentenyl groups. Examples of the aralkyl groups include benzyl, phenethyl, and phenylpropyl groups. The alkyl group, cycloalkyl group, unsaturated alkyl group, aralkyl group, etc. may have a substituent. Examples of the substituent include an alkoxy group and an acyl group. The number and the position of the substituent are not particularly limited as long as they do not impede the effects of the present invention. A straight-chain, branched-chain, or cyclic alkyl group having 1 to 8 carbon atoms is preferred.
[0019] R 6 ~R 8are each independently a branched alkyl group having 3 to 8 carbon atoms or a phenyl group. Examples of the branched alkyl group having 3 to 8 carbon atoms include an isopropyl group, an isobutyl group, a s-butyl group, a t-butyl group, a 2-methylbutyl group, an isopentyl group, a 2-ethylbutyl group, and a 3-methylpentyl group. In particular, R 6 ~R 8 As the alkyl group, an isopropyl group, a s-butyl group, a t-butyl group, and a phenyl group are preferable, and an isopropyl group is more preferable.
[0020] The component (A) is more preferably represented by the following general formula (I') or (II). [ka] [ka] In the above formula (I'), R 1’ R is a monovalent hydrocarbon group having 2 to 10 carbon atoms and a polymerizable unsaturated double bond. 1’ is preferably a monovalent hydrocarbon group having 2 to 6 carbon atoms, and more preferably the groups shown below. [ka] Particularly preferably, R 1’ is CH2=C(CH3)- or CH2=CH-. In the above formula (II), R 9 is the above R 5 or the above R 6 R 7 R 8 Si-, that is, a linear, branched, or cyclic alkyl group, an unsaturated alkyl group, an aralkyl group, or a triorganosilyl group having 1 to 8 carbon atoms, represented by R 6 R 7 R 8 Si- is a group represented by R 6 ~R 8 are each independently a branched alkyl group having 3 to 8 carbon atoms or phenyl.
[0021] In the above (I), (I') and (II), R 2 ~R 4 are each independently a linear or branched monovalent hydrocarbon group having 3 to 10 carbon atoms, preferably 3 to 8 carbon atoms, or a monovalent cyclic hydrocarbon group having 3 to 10 carbon atoms, preferably 3 to 8 carbon atoms. Examples of linear monovalent hydrocarbon groups include alkyl groups such as n-propyl, n-butyl, n-pentyl, hexyl, heptyl, and octyl. Branched monovalent hydrocarbon groups are preferably secondary or tertiary alkyl groups having a monovalent hydrocarbon group at the α- or β-position carbon atom. Here, the α-position carbon atom is the carbon atom bonded to the silicon atom in the above formula, and the β-position carbon atom is the carbon atom located next to the α-position carbon atom. The monovalent hydrocarbon group bonded to the α- or β-position carbon atom may be a methyl group, an ethyl group, or the like. Examples of the branched monovalent hydrocarbon group include an isopropyl group, an isobutyl group, a s-butyl group, a t-butyl group, a 2-methylbutyl group, an isopentyl group, a 2-ethylbutyl group, and a 3-methylpentyl group. Examples of the monovalent cyclic hydrocarbon group having 3 to 10 carbon atoms include a phenyl group, a benzyl group, and a cyclohexyl group. In particular, R 2 ~R 4 As the alkyl group, an isopropyl group, a s-butyl group, a t-butyl group, and a phenyl group are preferable, and an isopropyl group is more preferable.
[0022] Examples of the triorganosilyl group-containing monomer include triisopropylsilyl group-containing monomers, triisobutylsilyl group-containing monomers, tris-butylsilyl group-containing monomers, triisopentylsilyl group-containing monomers, triphenylsilyl group-containing monomers, diisopropylisobutylsilyl group-containing monomers, diisopropyls-butylsilyl group-containing monomers, diisopropylisopentylsilyl group-containing monomers, diisopropylphenylsilyl group-containing monomers, isopropyldiisobutylsilyl group-containing monomers, isopropyldis-butylsilyl group-containing monomers, t-butyldiisobutylsilyl group-containing monomers, t-butyldiisopentylsilyl group-containing monomers, and t-butyldiphenylsilyl group-containing monomers. These triorganosilyl group-containing monomers can be used alone or in combination of two or more. Among these, triisopropylsilyl group-containing monomers, tris-butylsilyl group-containing monomers and t-butyldiphenylsilyl group-containing monomers are particularly preferred, and triisopropylsilyl group-containing monomers are more preferred. In particular, from the viewpoints of production process, production cost, availability of raw materials and environmental safety, the triorganosilyl group-containing monomer is preferably R 2 ~R 4 Triisopropylsilyl group-containing monomers in which all the groups are isopropyl groups are preferred.
[0023] Examples of the component (A) include triisopropylsilyl (meth)acrylate, triisopropylsilyl 4-pentenoate, bis(triisopropylsilyl) maleate, methyl triisopropylsilyl maleate, ethyl triisopropylsilyl maleate, n-butyl triisopropylsilyl maleate, isobutyl triisopropylsilyl maleate, t-butyl triisopropylsilyl maleate, n-pentyl triisopropylsilyl maleate, isopentyl tripropylsilyl maleate, and 2-ethylhexyl maleate. Examples of the silyl triisopropylsilyl include cyclohexyl triisopropylsilyl maleate, bis(triisopropylsilyl) fumarate, methyl triisopropylsilyl fumarate, ethyl triisopropylsilyl fumarate, n-butyl triisopropylsilyl fumarate, isobutyl triisopropylsilyl fumarate, n-pentyl triisopropylsilyl fumarate, isopentyl triisopropylsilyl fumarate, 2-ethylhexyl triisopropylsilyl fumarate, and cyclohexyl triisopropylsilyl fumarate. These can be used alone or in combination of two or more. In particular, triisopropylsilyl (meth)acrylate is preferred. The term triisopropylsilyl (meth)acrylate means triisopropylsilyl acrylate or triisopropylsilyl methacrylate.
[0024] The amount of component (A) is 20 to 80 parts by mass, and preferably 40 to 75 parts by mass, per 100 parts by mass of the total of components (A) to (C). If the amount is less than 20 parts by mass, the resulting coating may not have sufficient water resistance and salt water resistance, and if it exceeds 80 parts by mass, the MFT of the acrylic resin emulsion may exceed 50°C.
[0025] (B) (Meth)acrylic acid alkyl ester monomer having no functional group The component (B) is an alkyl acrylate monomer and / or an alkyl methacrylate monomer (hereinafter sometimes referred to as an acrylic component). It is an alkyl acrylate monomer or an alkyl methacrylate monomer that does not have a functional group such as a hydroxy group, an alkoxy group, an amide group, or a carboxy group. It preferably has an alkyl group having 1 to 10 carbon atoms at the ester terminal. It is preferable that the acrylic component is a monomer whose polymer has a glass transition temperature (hereinafter sometimes referred to as Tg) of 40°C or higher, preferably 60°C or higher. Examples of such monomers include methyl methacrylate, isopropyl methacrylate, ethyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl acrylate, and butyl acrylate. The upper limit of Tg is preferably 200°C or lower, more preferably 150°C or lower. The glass transition temperature can be measured based on JIS K7121.
[0026] The amount of component (B) is 20 to 80 parts by mass, and preferably 25 to 75 parts by mass, per 100 parts by mass of the total of components (A) to (C). If the amount is less than 20 parts by mass, the emulsion polymerization reaction may not proceed well, and if the amount is more than 80 parts by mass, the resulting coating may not have water resistance.
[0027] In addition, other monomers (C) containing functional groups that are copolymerizable with the above-mentioned (A) and (B) components can be copolymerized. The (C) component may be a monomer having an unsaturated bond that may have a functional group such as a carboxy group, an amide group, a hydroxy group, an alkoxy group, a vinyl group, or an allyl group. Examples of such monomers include methacrylic acid, acrylic acid, acrylamide, allyl methacrylate, vinyl methacrylate, 2-methoxyethyl acrylate (methoxyethyl acrylate), 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. By copolymerizing these, it is possible to improve the compatibility between the core-shell resin and the thermoplastic resin. Preferred are methacrylic acid, acrylic acid, 2-methoxyethyl acrylate, and 2-hydroxyethyl methacrylate.
[0028] The amount of component (C) is 0 to 60 parts by mass, preferably 0.5 to 30 parts by mass, or 1 to 25 parts by mass, or even 5 to 20 parts by mass, relative to 100 parts by mass of the total of (A) to (C) above. If the amount exceeds 60 parts by mass, the emulsion becomes unstable and polymerization cannot be carried out.
[0029] (D) Polymer emulsifier The component (D) may be a known polymeric emulsifier. The polymeric emulsifier is an emulsifier having a high molecular weight as described above, and more specifically, a polymeric compound having emulsifying properties. The high molecular weight is a number (or weight) average molecular weight of 1,000 or more, preferably 1,000 to 200,000. The lower limit of the number average molecular weight is more preferably 3,000 or more, and even more preferably 5,000 or more. The upper limit is preferably 100,000 or less, more preferably 80,000 or less, and even more preferably 50,000 or less. If the molecular weight of the emulsifier is less than the lower limit, there is a risk of problems such as the generation of aggregates, and if it exceeds the upper limit, there is a risk of problems such as the generation of a large amount of aggregates, and in the worst case, gelation. The number average molecular weight is a polystyrene equivalent value measured by GPC. In addition, in the present invention, a compound having a molecular weight of 50,000 or less is called an oligomer.
[0030] Examples of the polymer emulsifier include one or more polymer emulsifiers selected from a carboxyl group-containing (co)polymer or its salt, a carboxylate-containing (co)polymer, and a urethane resin. More preferred examples include one or more polymer compounds selected from poly(meth)acrylic acid, poly(meth)acrylates, poly(meth)acrylates, styrene-(meth)acrylic acid copolymers, styrene-(meth)acrylate copolymers, styrene-(meth)acrylate copolymers, styrene-(meth)acrylic acid ester copolymers, and polyurethane resins.
[0031] Examples of emulsifiers containing poly(meth)acrylates, poly(meth)acrylate esters, styrene-(meth)acrylic acid copolymers, styrene-(meth)acrylate copolymers, and styrene-(meth)acrylate ester copolymers include JONCRYL JDX-6500 (non-volatile content 30%), JONCRYL JDX-6102B (non-volatile content 24.5%), JONCRYL HPD-96J (non-volatile content 34%), and JONCRYL 52J (non-volatile content 60%) (all manufactured by BASF), E-1048, and HE-1335 (non-volatile content 45.5%) (Seiko PMC Corporation, etc.).
[0032] An example of the poly(meth)acrylic acid is Aron (a polyacrylic acid-based product manufactured by Toagosei Co., Ltd.).
[0033] An example of the polyurethane resin is Hydran WLS-213 (manufactured by DIC Corporation, non-volatile content 34% to 36%).
[0034] The amount of the polymer emulsifier (D) is 5 to 70 parts by mass, preferably 20 to 60 parts by mass, per 100 parts by mass of the total of the components (A) to (C). When the polymer emulsifier and the solvent are contained as in the above commercially available product, the amount of solid content is 5 to 70 parts by mass, preferably 20 to 60 parts by mass, per 100 parts by mass of the total of the components (A) to (C). If the amount is less than 5 parts by mass, there is a problem that a large amount of the acrylic monomer remains unreacted.
[0035] The acrylic resin emulsion of the present invention is obtained by emulsifying and polymerizing the above-mentioned components (A) and (B), and optionally the component (C), in the presence of the polymer emulsifier (D). In detail, a mixture of the components (A) and (B), and optionally the component (C), is reacted with the polymer emulsifier (D) in the presence of a radical initiator at 50 to 90°C while being added dropwise 2 to 10 times or continuously within a predetermined time (from 3 hours).
[0036] Examples of the radical initiator include persulfates such as potassium persulfate and ammonium persulfate, hydrogen persulfate water, t-butyl hydroperoxide, hydrogen peroxide, benzoyl peroxide, AIBN, etc. If necessary, a redox system using a reducing agent such as sodium sulfite, Rongalite, L-ascorbic acid, tartaric acid, sugars, and amines in combination can also be used.
[0037] Additionally, a chain transfer agent may be added to adjust the molecular weight of the polymer.
[0038] The polymerization temperature is preferably from 50 to 90°C, more preferably from 50 to 70°C.
[0039] The acrylic resin emulsion of the present invention has an average particle size of 300 nm or less, preferably 50 to 250 nm, and more preferably 50 to 200 nm. If the average particle size is too large, a transparent coating material cannot be obtained, and if it is too small, there is a problem of reduced dispersibility. It is also possible to micronize the emulsion by known methods such as a starburst, high-pressure homogenizer, continuous emulsifier, colloidal mill, and kneader. The average particle size of the emulsion can be measured by dynamic light scattering using, for example, FPAR-1000 manufactured by Otsuka Electronics Co., Ltd.
[0040] The acrylic resin emulsion of the present invention preferably has a minimum film-forming temperature (MFT) of 50°C or less. It is preferably 0 to 50°C, more preferably 0 to 20°C, and even more preferably 0 to 15°C. This allows a film to be formed well even at room temperature or in a low air temperature environment. If the MFT exceeds the upper limit, there is a risk that cracks will occur in the coating film when it is dried at room temperature. The minimum film-forming temperature is the minimum temperature at which a crack-free, uniform film is formed when the coating composition is dried, and can be measured by the method described in JIS K 6828-2:2003.
[0041] The solid content of the acrylic resin emulsion is preferably 25 to 50% by mass. The viscosity (25°C) is preferably 500 mPa·s or less, more preferably 20 to 300 mPa·s. The viscosity can be measured by a rotational viscometer. The remainder of the emulsion is water, and may contain an organic solvent as necessary. The amount of water is not particularly limited, and is preferably an amount that results in a solid content of the emulsion of 25 to 50% by mass.
[0042] The acrylic resin emulsion of the present invention has good long-term storage stability and is capable of forming a coating film excellent in transparency, water resistance, salt water resistance and water repellency, and is therefore suitably used as a coating composition.
[0043] In addition to the acrylic resin emulsion, other organic resins, antifouling agents, pigments, plasticizers, and other additives can be used in the coating composition of the present invention.
[0044] The other organic resins are not particularly limited, but examples thereof include synthetic resins such as chlorinated rubber, vinyl chloride-vinyl acetate copolymer, and vinyl chloride-isobutyl vinyl ether copolymer, and natural resins such as rosin, rosin metal salts, and modified rosin, which may be used alone or in combination of two or more kinds.
[0045] Examples of the antifouling agent include copper compounds such as cuprous oxide, copper rhodanide, copper powder, and 2-mercaptopyridine-N-oxide copper, zinc compounds such as 2-mercaptopyridine-N-oxide zinc, bisdimethyldithiocarbamoylzinc ethylene bisdithiocarbamate, and zinc dimethyldithiocarbamate, and metal-free compounds such as 2,4,5,6-tetrachloroisophthalonitrile, 3,4-dichlorophenyldimethylurea, 4,5-dichloro-2-N-octyl-3-(2H)-isothiazoline, N,N-dimethyl-N'-phenyl(N-fluorodichloromethylthio)sulfamide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, 3-iodo-2-propynyl butylcarbamate, pyridinetriphenylborane, and 2-(methoxycarbonylamino)benzimidazole, which may be used alone or in combination of two or more.
[0046] The pigment is not particularly limited, but examples thereof include red iron oxide, talc, acid Examples of the inorganic fillers include titanium dioxide, silica, calcium carbonate, barium sulfate, calcium oxide, and zinc oxide, and these can be used alone or in combination of two or more.
[0047] The plasticizer and other additives are not particularly limited, but may be, for example, Examples of such additives include plasticizers such as ricresyl phosphate, dioctyl phthalate, chlorinated paraffin, liquid paraffin, and polybutene, thixotropic agents such as bentonite, polyethylene oxide, and various amide compounds, dyes, defoamers, water binding agents, and organic solvents, and these can be used alone or in combination of two or more.
[0048] When the coating composition of the present invention is applied or immersed on one or both sides of a substrate such as plastics (PET, PI, synthetic leather, etc.), glass (general-purpose glass, SiO2, etc.), metals (Si, Cu, Fe, Ni, Co, Au, Ag, Ti, Al, Zn, Sn, Zr, alloys thereof, etc.), wood, paper, ceramics (fired products of oxides, carbides, nitrides, etc.), and then dried (room temperature to 150°C), it is possible to impart the advantage of the water resistance of the resin to the substrate for a long period of time while maintaining the advantages of the substrate.
[0049] Here, examples of metal materials include SUS, SPHC, etc. Examples of applications for coating metal materials include ship bottoms, ship hulls, vehicle fittings, car bodies, building materials, etc.
[0050] Examples of plastic substrates that can be used include poly(meth)acrylic acid esters such as polymethyl methacrylate, polycarbonate, polystyrene, polyethylene terephthalate, polyvinyl chloride, polyester, cellulose, diethylene glycol bisallyl carbonate polymer, acrylonitrile-butadiene-styrene polymer, polyurethane, and epoxy resin. Examples of plastic processed products include automotive interior materials, organic glass, electrical materials, building materials, exterior materials for buildings, optical films used in liquid crystal displays, and the like, light diffusion films, mobile phones, and home appliances.
[0051] Examples of glass substrates that can be used include soda-lime glass, quartz glass, lead glass, borosilicate glass, alkali-free glass, etc. Examples of glass processed products include architectural plate glass, glass for vehicles such as automobiles, glass for lenses, glass for mirrors, glass for display panels, glass for solar cell modules, etc.
[0052] As the wood substrate, wood from the families Maple, Betulaceae, Lauraceae, Chestnut, Scrophulariaceae, Araucaria, Ulmaceae, Bignoniaceae, Rosaceae, Cupressaceae, Dipterocarpaceae, Myrtaceae, Fagaceae, Pinaceae, Fabaceae, Oleaceae, etc. is used. The wood processed product may be selected from processed and molded products made from wood itself as a raw material, plywood and laminated lumber, processed and molded products thereof, and combinations thereof, and includes, for example, building materials including materials for the exterior and interior of buildings, furniture such as desks, wooden toys, musical instruments, etc.
[0053] The method for coating the coating composition of the present invention onto a substrate is not particularly limited, and examples thereof include coating methods using various coaters such as a gravure coater, a bar coater, a blade coater, a roll coater, an air knife coater, a screen coater, a curtain coater, and brush coating, spray coating, immersion, and the like.
[0054] The amount of the coating composition of the present invention to be applied to a substrate is not particularly limited. In general, from the viewpoint of workability and the like, it is preferably 1 to 300 g / m2 in terms of solid content. 2 , more preferably 5 to 100 g / m 2 The film may be formed by drying at room temperature, or by drying by heating at 100 to 200° C., to have a thickness of 1 to 500 μm, and preferably 5 to 100 μm.
[0055] The coating composition of the present invention is particularly suitable for use as a coating for articles used in water and seawater, and is suitable as an underwater coating and an undersea coating. In particular, the coating film obtained from the coating composition of the present invention has good saltwater resistance, and is suitable as an undersea antifouling coating to be applied to the surfaces of undersea articles such as the bottom of a ship, an undersea structure, a power plant water pipe, aquaculture or fixed fishing nets, or fishing net accessories such as floats and ropes used therefor. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, parts and % respectively indicate parts by mass and % by mass.
[0057] [Acrylic resin emulsion] [Example 1] A 2L glass flask equipped with a stirrer, thermometer, and reflux condenser was filled with 770g of ion-exchanged water, 2g of sodium carbonate, and 630g of JDX-6500 (polyacrylic acid oligomer, number average molecular weight 10000, non-volatile content 30%), and the container was replaced with nitrogen, and heated with stirring by a stirrer until the temperature of the internal solution reached 60°C. While maintaining the temperature of the internal solution at 60°C ± 1°C, a mixture of 70g of 2-ethylhexyl acrylate (2-EHA), 87.5g of methoxyethyl acrylate (MEA), and 192.5g of triisopropylsilyl methacrylate (TIPSMA) was added dropwise using a dropping funnel over 3 hours, while 1g of ammonium persulfate (APS) dissolved in 45g of ion-exchanged water was added dropwise over 4 hours, and the mixture was emulsion-polymerized. After the reaction was completed, the mixture was cooled to below 40°C and dried at 105°C for 1 hour to obtain a milky white acrylic resin emulsion having a non-volatile content (solid content) of 31%.
[0058] [Example 2] A 2L glass flask equipped with a stirrer, thermometer, and reflux condenser was filled with 770g of ion-exchanged water, 2g of sodium carbonate, and 291.5g of JDX-6500 (polyacrylic acid oligomer, number average molecular weight 10000, non-volatile content 30%), and the container was replaced with nitrogen, and heated with stirring by a stirrer until the temperature of the internal solution reached 60°C. While maintaining the temperature of the internal solution at 60°C ± 1°C, a mixture of 87.5g of methylbutyl acrylate (BA), 70g of methoxyethyl acrylate (MEA), and 192.5g of triisopropylsilyl methacrylate (TIPSMA) was added dropwise using a dropping funnel over 3 hours under a nitrogen stream, while 1g of ammonium persulfate (APS) dissolved in 45g of ion-exchanged water was added dropwise over 4 hours, and the mixture was emulsion-polymerized. After the reaction was completed, the mixture was cooled to below 40°C and dried at 105°C for 1 hour to obtain a milky white acrylic resin emulsion having a non-volatile content (solid content) of 29%.
[0059] [Example 3] A 2L glass flask equipped with a stirrer, thermometer, and reflux condenser was filled with 770g of ion-exchanged water, 2g of sodium carbonate, and 630g of JDX-6500 (polyacrylic acid oligomer, number average molecular weight 10000, non-volatile content 30%). The container was replaced with nitrogen, and heated with stirring by a stirrer until the temperature of the internal solution reached 60°C. While maintaining the temperature of the internal solution at 60°C ± 1°C, a mixture of 87.5g of 2-ethylhexyl acrylate (2-EHA) and 262.5g of triisopropylsilyl methacrylate (TIPSMA) was added dropwise using a dropping funnel over 3 hours under a nitrogen stream, while 1g of ammonium persulfate (APS) dissolved in 45g of ion-exchanged water was added dropwise over 4 hours to emulsion-polymerize the mixture. After the reaction was completed, the mixture was cooled to below 40°C, and dried at 105°C for 1 hour to obtain a milky white acrylic resin emulsion having a non-volatile content (solid content) of 30%.
[0060] [Example 4] A 2L glass flask equipped with a stirrer, thermometer, and reflux condenser was filled with 770g of ion-exchanged water, 2g of sodium carbonate, and 630g of JDX-6500 (polyacrylic acid oligomer, number average molecular weight 10000, non-volatile content 30%). The container was replaced with nitrogen, and heated with stirring by a stirrer until the temperature of the internal solution reached 60°C. While maintaining the temperature of the internal solution at 60°C ± 1°C, a mixture of 262.5g of 2-ethylhexyl acrylate (2-EHA) and 87.5g of triisopropylsilyl methacrylate (TIPSMA) was added dropwise using a dropping funnel over 3 hours under a nitrogen stream, while 1g of ammonium persulfate (APS) dissolved in 45g of ion-exchanged water was added dropwise over 4 hours to emulsion-polymerize the mixture. After the reaction was completed, the mixture was cooled to below 40°C, and dried at 105°C for 1 hour to obtain a milky white emulsion with a non-volatile content (solid content) of 30%.
[0061] [Example 5] A 2L glass flask equipped with a stirrer, thermometer, and reflux condenser was filled with 770g of ion-exchanged water, 2g of sodium carbonate, and 630g of WLS-213 (urethane resin, number average molecular weight 25000, non-volatile content 30%), and the container was replaced with nitrogen, and heated with stirring by a stirrer until the temperature of the internal solution reached 60° C. While maintaining the temperature of the internal solution at 60° C.±1° C., a mixture of 70g of 2-ethylhexyl acrylate (2-EHA), 87.5g of methoxyethyl acrylate (MEA), and 192.5g of triisopropylsilyl methacrylate (TIPSMA) was added dropwise using a dropping funnel over 3 hours, while 1g of ammonium persulfate (APS) dissolved in 45g of ion-exchanged water was added dropwise over 4 hours, and the mixture was emulsion-polymerized. After the reaction was completed, the mixture was cooled to below 40°C and dried at 105°C for 1 hour to obtain a milky white emulsion having a non-volatile content (solid content) of 30%.
[0062] [Comparative Example 1] A 2L glass flask equipped with a stirrer, thermometer, and reflux condenser was filled with 770g of ion-exchanged water, 2g of sodium carbonate, and 630g of JDX-6500 (polyacrylic acid oligomer, number average molecular weight 10000, non-volatile content 30%). The container was replaced with nitrogen and heated with stirring by a stirrer until the temperature of the internal solution reached 60°C. While maintaining the temperature of the internal solution at 60°C±1°C, 350g of methyl methacrylate was dropped using a dropping funnel over 3 hours under a nitrogen stream, while 1g of ammonium persulfate (APS) dissolved in 45g of ion-exchanged water was dropped over 4 hours to emulsion-polymerize the mixture. After the reaction was completed, the mixture was cooled to below 40°C and dried at 105°C for 1 hour to obtain a milky white emulsion with a non-volatile content (solid content) of 30%.
[0063] [Comparative Example 2] A 3L polymerization vessel equipped with a stirrer, a condenser, a thermometer, and a nitrogen gas inlet was charged with 500g of ion-exchanged water, and the vessel was substituted with nitrogen gas for 15 minutes, and then heated to 70°C. Next, in a separate vessel, 70g of 2-ethylhexyl acrylate (2-EHA), 87.5g of methoxyethyl acrylate (MEA), 192.5g of triisopropylsilyl methacrylate (TIPSMA), 3g of Sanmorin OT-70 (Kao Corporation), 16g of Noigen XL-41 (Daiichi Kogyo Seiyaku Co., Ltd.), 28g of Noigen XL-400 (Daiichi Kogyo Seiyaku Co., Ltd.), and 400g of ion-exchanged water were mixed and emulsified with a homogenizer to obtain an emulsion. The emulsion and a mixture of 3g of potassium persulfate and 100g of ion-exchanged water were separately dropped uniformly into the polymerization vessel while stirring for 4 hours. The mixture was then reacted at 70°C for 2 hours to complete the polymerization. After cooling, 25% aqueous ammonia was added to adjust the pH to 7. The solids content of the resulting synthetic resin emulsion was 40.4%.
[0064] [Comparative Example 3] A 2L glass flask equipped with a stirrer, thermometer, and reflux condenser was filled with 770g of ion-exchanged water, 2g of sodium carbonate, and 630g of JDX-6500 (polyacrylic acid oligomer, number average molecular weight 10000, non-volatile content 30%). The container was replaced with nitrogen, and heated with stirring by a stirrer until the temperature of the internal solution reached 60°C. While maintaining the temperature of the internal solution at 60°C ± 1°C, a mixture of 192.5g of methyl methacrylate, 140g of methoxyethyl acrylate (MEA), and 17.5g of triisopropylsilyl methacrylate (TIPSMA) was added dropwise using a dropping funnel over 3 hours under a nitrogen stream, while 1g of ammonium persulfate (APS) dissolved in 45g of ion-exchanged water was added dropwise over 4 hours to emulsion-polymerize the mixture. After the reaction was completed, the mixture was cooled to below 40°C, and dried at 105°C for 1 hour to obtain a milky white emulsion with a non-volatile content (solid content) of 29%.
[0065] [Comparative Example 4] A 2L glass flask equipped with a stirrer, thermometer, and reflux condenser was filled with 770g of ion-exchanged water, 2g of sodium carbonate, and 933g of JDX-6500 (polyacrylic acid oligomer, number average molecular weight 10000, non-volatile content 30%). The container was replaced with nitrogen and heated with stirring by a stirrer until the temperature of the internal solution reached 60°C. While maintaining the temperature of the internal solution at 60°C ± 1°C, 350g of triisopropylsilyl methacrylate (TIPSMA) was dropped over 3 hours using a dropping funnel under a nitrogen stream, while 1g of ammonium persulfate (APS) dissolved in 45g of ion-exchanged water was dropped over 4 hours to emulsion-polymerize triisopropylsilyl methacrylate. After the reaction was completed, the mixture was cooled to below 40°C, and a milky white emulsion with a non-volatile content (solid content) of 29% was obtained after drying at 105°C for 1 hour.
[0066] <Method of measuring solid content> Approximately 1 g of each resin emulsion (sample) was accurately weighed onto an aluminum foil dish, placed in a dryer maintained at approximately 105°C, heated for 1 hour, then removed from the dryer and allowed to cool in a desiccator. The sample was then weighed after drying, and the evaporation residue was calculated using the following formula.
number
[0067] <Method for measuring pH> The pH of each emulsion was measured at 25 °C using a pH meter in accordance with JIS Z8802 (Method for measuring pH).
[0068] <Method for measuring the minimum film-forming temperature (MFT)> The minimum film-forming temperature (MFT) of the emulsion was measured by a method conforming to JIS K-6828-2. Specifically, a simple film-forming temperature measuring device (manufactured by Imoto Seisakusho) in which a heating source and a cooling source were installed at a certain distance was used. The emulsion was applied to an aluminum foil at a thickness of 1 mil, and the state of the coating film after 2 h was observed using the device. The emulsion was dried under temperature control to form a film, and the boundary temperature between the transparent part and the non-film-forming part was measured as the minimum film-forming temperature (MFT, °C).
[0069] <Method for measuring the average particle diameter of emulsion particles> The obtained emulsion was further diluted with ion-exchanged water to a solution with a solid content of 0.5 - 2%, and the emulsion particle diameter was measured by the dynamic light scattering method using a FPAR-1000 manufactured by Otsuka Electronics Co., Ltd.
[0070] <Evaluation of stability over time> The emulsion was stored at room temperature (25 °C) for 3 months. The average particle diameter of the emulsion after storage was measured by the method described above. Those in which the particle diameter does not increase by more than 20% with respect to the emulsion immediately after production are evaluated as ○.
[0071] <Film-forming method> An epoxy resin-based rust-preventive paint (Banno 500S, Chugoku Toryo Co., Ltd.) was brushed onto a steel plate (Nippon Test Panel Co., Ltd., SPHC double-sided sandblasted) to a dry film thickness of 100 μm. After drying, an emulsion was brushed onto the film to a dry film thickness of 100 μm, and then dried at room temperature to prepare a coating film sample.
[0072] <Haze value measurement> The emulsion was applied to a slide glass (haze value 0.70%) to a dry film thickness of about 7 μm, and dried at room temperature using a bar coater No. 10 to form a coating film. The haze value of the slide glass having the coating film was measured using a product called "Haze Meter NDH7000" (manufactured by Nippon Denshoku Industries Co., Ltd.).
[0073] <Measurement of water contact angle> A 0.2 μL drop of water was dropped onto the coating sample, and the contact angle 30 seconds later was measured using an automatic contact angle meter DCA-VZ manufactured by Kyowa Interface Science Co., Ltd.
[0074] <Saltwater resistance> The above coating sample was immersed in 3.5% sodium chloride dissolved in ion-exchanged water, which was assumed to be seawater, for several days, and the condition of the coating was visually observed. If there was no whitening, peeling, or cracking, it was deemed to be no problem, and observations were continued. When abnormalities in the coating such as whitening, peeling, or cracking were confirmed, the observation was stopped and marked as the end point. The number of days until the end point is shown in Table 1.
[0075] [Table 1] TIPSMA: Triisopropylsilyl methacrylate (Shin-Etsu Chemical Co., Ltd.) MMA: Methyl methacrylate BA: Butyl acrylate 2-EHA: 2-ethylhexyl acrylate MEA: Methoxyethyl acrylate JDX-6500: BASF polyacrylate oligomer (number average molecular weight 10,000) WLS-213: DIC Hydran WLS-213 water-based polyurethane resin (number average molecular weight 25,000)
[0076] [Example 6] 25 parts of ion-exchanged water, 2 parts of BYK-190 (wetting dispersant, Byk-Chemie), 20 parts of titanium oxide (Typaque CR-95 (Ishihara Sangyo Kaisha), average particle size 0.28 μm, rutile-type titanium oxide), 100 parts of talc MS (Nippon Talc Co., Ltd.) and glass beads (diameter: 1 mm) were dispersed in a homodisper at a rotation speed of 3000 rpm for 60 minutes, and then filtered through a 100-mesh wire screen to prepare a white paste. 371 parts of the emulsion obtained in Example 1 were added thereto to obtain a coating composition. [Examples 7 to 10, Comparative Examples 6 to 9] A coating composition was obtained by repeating Example 6 above, except that the emulsion was changed to the formulation shown in Table 2 below.
[0077] <Film formation method> An epoxy resin-based rust-preventive paint (Banno 500S, Chugoku Toryo Co., Ltd.) was brushed onto a steel plate (SPHC double-sided sandblasted, manufactured by Nippon Test Panel Co., Ltd.) to a dry film thickness of 100 μm. After drying, the above-mentioned coating composition was brushed onto the coating to a dry film thickness of 100 μm, and then dried at room temperature to obtain a coating sample.
[0078] The water contact angle and salt water resistance of each coating sample were evaluated by the methods described above, and the results are shown in Table 2.
[0079] [Table 2]
[0080] As shown in Tables 1 and 2, the acrylic resin emulsion of the present invention can provide a coating film having transparency, water resistance, salt water resistance, and water repellency, and further has excellent long-term storage stability. In addition, since the acrylic resin emulsion of the present invention has a minimum film-forming temperature (MFT) of 50°C or less, it can form a good film even at room temperature.
Claims
1. (A) 20 to 80 parts by mass of a triorganosilyl ester monomer having a polymerizable unsaturated double bond and a monovalent hydrocarbon group having 2 to 24 carbon atoms which may have a heteroatom, (B) 20 to 80 parts by mass of a (meth)acrylic acid alkyl ester monomer having no functional group, and (C) 0 to 60 parts by mass of a monomer having an unsaturated bond, other than components (A) and (B), which may have a functional group selected from a carboxy group, an amide group, a hydroxy group, an alkoxy group, a vinyl group, and an allyl group (however, the total of (A) to (C) is 100 parts by mass). Acrylic resin, which is a polymer of (D) one or more polymer emulsifiers selected from poly(meth)acrylic acid, poly(meth)acrylates, poly(meth)acrylic acid esters, styrene-(meth)acrylic acid copolymers, styrene-(meth)acrylate copolymers, styrene-(meth)acrylic acid ester copolymers, and polyurethane resins, each having a number average molecular weight of 5,000 to 50,000; 5 to 70 parts by mass per 100 parts by mass of the total of the components (A) to (C); and water.
2. The acrylic resin emulsion according to claim 1, wherein the component (A) is represented by the following general formula (I): 【Chemistry 1】 (R 1 is a monovalent organic group having a polymerizable unsaturated double bond, having 2 to 24 carbon atoms, and optionally having a heteroatom; R 2 ~R 4 are each independently a monovalent linear or branched hydrocarbon group having 3 to 10 carbon atoms, or a monovalent cyclic hydrocarbon group having 3 to 10 carbon atoms.
3. The acrylic resin emulsion according to claim 1 or 2, which has a minimum film-forming temperature (MFT) of 0 to 50°C.
4. The acrylic resin emulsion according to any one of claims 1 to 3, wherein the component (B) is a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 10 carbon atoms.
5. The acrylic resin emulsion according to any one of claims 1 to 4, wherein the component (C) is selected from methacrylic acid, acrylic acid, acrylamide, allyl methacrylate, vinyl methacrylate, 2-methoxyethyl acrylate (methoxyethyl acrylate), 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate.
6. A coating composition comprising the acrylic resin emulsion according to any one of claims 1 to 5.
7. (A) a triorganosilyl ester monomer having a polymerizable unsaturated double bond and having a monovalent hydrocarbon group having 2 to 24 carbon atoms which may have a heteroatom, (B) a (meth)acrylic acid alkyl ester monomer having no functional group, and (C) an arbitrary monomer having an unsaturated bond which may have a functional group selected from a carboxy group, an amide group, a hydroxy group, an alkoxy group, a vinyl group, and an allyl group, other than the above components (A) and (B), in an amount of solid content per 100 parts by mass of components (A), (B), and (C). and (D) one or more polymer emulsifiers selected from poly(meth)acrylic acid, poly(meth)acrylates, poly(meth)acrylic acid esters, styrene-(meth)acrylic acid copolymers, styrene-(meth)acrylate copolymers, styrene-(meth)acrylic acid ester copolymers, and polyurethanes, each of which has a number average molecular weight of 5,000 or more and 50,000 or less, in an amount of 5 to 70 parts by mass, to obtain an emulsion of an acrylic resin.
8. The method according to claim 7, wherein the component (A) is represented by the following general formula (I): 【Chemistry 2】 (R 1 is a monovalent organic group having a polymerizable unsaturated double bond, having 2 to 24 carbon atoms, and optionally having a heteroatom; R 2 ~R 4 are each independently a monovalent linear or branched hydrocarbon group having 3 to 10 carbon atoms, or a monovalent cyclic hydrocarbon group having 3 to 10 carbon atoms.
9. The method according to claim 7 or 8, wherein the acrylic resin emulsion has a minimum film-forming temperature (MFT) of 0 to 50°C.
10. A method for producing a polymer according to any one of claims 7 to 9, wherein the component (B) is a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 10 carbon atoms.
11. The method according to any one of claims 7 to 10, wherein the component (C) is selected from methacrylic acid, acrylic acid, acrylamide, allyl methacrylate, vinyl methacrylate, 2-methoxyethyl acrylate (methoxyethyl acrylate), 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate.
Citation Information
Patent Citations
Polymeric emulsifier for emulsion polymerization
JP1993320261A
Water-resistant aqueous emulsion composition and its production
JP1995268022A
Antifouling coating composition, coating film formed from the same, antifouling method using the same, and hull or underwater structure coated with the same
JP1997048946A
Antifouling coating composition and submarine articles coated with the composition, and antifouling method using the composition
JP2005082725A
Method for producing aqueous dispersion of resin containing triorganosilyl
JP2006052284A